Pengaruh Penambahan Akuades Terhadap Lapisan Hidroksiapatit Pada Permukaan Logam - Ines Indriyani; Komalasari Komalasari; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
316L stainless steel is a material that can be used as an implant because it has strong mechanical properties but does not have bioactive properties so it needs to be coated with hydroxyapatiteon the surface of 316L stainless steel. The aim of the study was to determine the effect of weight ratio of hydroxyapatite and distilled water to the thickness of the hydroxyapatite layer. The method used in the study starts from the preparation of the dipping solution then the substrate was installed in the dip coating unit and the dipping processbegins. The fixed variables used in this research are the amount of HAp weight that is 12 grams, the stirring time is 20 hours, and the sintering time is 1 hour. While the changeable variables used in this study are the amount of aquades by 24 and 28 grams. Parameters has a significant effect on layer coating thickness which gives 29,6% change in the thickness of the HAp layer. The more addition of distilled water to the coating solution, the thickness of the HAp layer decreases and vice versa.Keywords : dip coating, hydroxyapatite, implan, steel